The science of live written on birds. fourth part: undulated tinamou (crypturellus undulatus) (2014)
Bilingual text Muinane-Spanish about the bird species kɨɨñu, “undulated tinamou” (Crypturellus undulatus), written by Aniceto Nejedeka, based on the knowledge of the elders of the Muinane tribe. This text is the fourth part of a book, titled The science of life written on birds, which we have been publishing is fascicles. Muinane is a language of the Bora linguistic family.